2006
DOI: 10.1021/jp063441z
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photocatalytic Degradation of Phenol over Co3O4/BiVO4 Composite under Visible Light Irradiation

Abstract: Co3O4/BiVO4 composite photocatalyst with a p-n heterojunction semiconductor structure has been synthesized by the impregnation method. The physical and photophysical properties of the composite photocatalyst have been characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transimission electron microscopy (TEM), BET surface area, and UV-visible diffuse reflectance spectra. Co is present as p-type Co3O4 and disperses on the surface of n-type BiVO4 to constitute a heterojunction compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
378
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 846 publications
(404 citation statements)
references
References 44 publications
23
378
1
2
Order By: Relevance
“…This is due to the smaller bandgap of Co3O4, previously reported to be 2.07 eV. 21 From the absorbance data, a Tauc plot is generated for WO3 film using the following equations: where α is the absorption coefficient, A is the film absorbance, E is the photon energy, Eg is the band gap and the exponential γ equals to 0.5 for indirect band gap material. With the Tauc plot, the band gap of the deposited WO3 film is determined to be 2.6 eV which is similar to reported works in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the smaller bandgap of Co3O4, previously reported to be 2.07 eV. 21 From the absorbance data, a Tauc plot is generated for WO3 film using the following equations: where α is the absorption coefficient, A is the film absorbance, E is the photon energy, Eg is the band gap and the exponential γ equals to 0.5 for indirect band gap material. With the Tauc plot, the band gap of the deposited WO3 film is determined to be 2.6 eV which is similar to reported works in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In the above equation, n is a constant and is dependent on the type of semiconductor. In the case of BiVO 4 , n is equal to 0.5 and 2 for direct and indirect band gap, respectively [26]. The band gap for the pure and Co-doped BiVO 4 was estimated to be 2.44, 2.43, 2.42, and 2.39 eV at cobalt content of 0, 1%, 5%, and 10%, respectively.…”
Section: Sem Imaging Of Co-bivo 4 Photocatalystsmentioning
confidence: 98%
“…When cobalt oxides are in contact with an n-type semiconductor such as BiVO 4 , a p-n junction is formed and the recombination of hole-electron pairs is suppressed. Long et al [26] and Xu et al [27] studied the photocatalytic properties of Co-doped BiVO 4 and reported a significant increase in the photoreactivity of BiVO 4 . In this study, we prepared Co-doped BiVO 4 using the amorphous heteronuclear complexation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Using photocatalyst and co-catalyst materials in the nanocrystalline form also offers the attractive opportunity to minimize the distances (and thus the times) over which photo-induced electron-hole pairs have to survive and be transported to reactant molecules after photo-excitation. The formation of heterojunction structures between two nanostructured semiconductors with different band gaps and matching band potentials can also extend light absorption, improve charge separation, increase the lifetime of charge carriers, and enhance the interfacial charge-transfer efficiency (Long et al 2006;Tada et al 2006;Yang et al 2009). Deposition of noble metal nanoscale clusters on the photocatalyst surface has also been shown to enhance the photocatalytic activity owing to increased transfer rates of photo-generated electrons to the absorbed metal/semiconductor clusters, thus decreasing markedly the possibility of electron-hole recombination (Baba et al 1985;Zhang et al 2009).…”
Section: D) Photochemical Production Of Synthetic Fuelsmentioning
confidence: 99%